Proceso de atención de enfermería en paciente diabético que presenta oftalmomiasis en el área de medicina interna en el Hospital Básico Sagrado Corazón de Jesús - Rodríguez Buste, Eyda Melissa (2020)
The Nursing Care Process is considered a scientific method that allows the nurse to carry out care plans directly and individually, in a rational, logical and systematic way. The present clinical case shows results on the assessment of the nursing care process in a diabetic patient presenting ophthalmomiasis, for which purpose a clinical examination and the respective complementary examinations were carried out. The objective of the clinical case is to apply the nursing care process in a diabetic patient who presents ophthalmomiasis at the Sacred Heart of Jesus Hospital, for which a caudal cephalic evaluation was carried out followed by an evaluation by functional patterns of Jean Watson through which showed altered functional patterns with which the pertinent nursing diagnoses were carried out to develop nursing goals, objectives and interventions according to the needs of the patient. The follow-up is carried out in which all nursing interventions and a correct administration of medications prescribed by the doctor are fulfilled. The nursing care process is established as a systematic and organized method of administering comprehensive and progressive nursing care; it focuses on the identification and treatment of responses to health needs.